Contribution à la simulation et la modélisation du contrôle d'un système de pile à combustible à membrane échangeuse de protons Contribution to the simulation and control modeling of a proton exchange membrane fuel cell system - Mohammed Yousri Silaa; Prof. Ali Cheknane Supervisor University of Amar Telidji, Laghouat, Algeria Dr. Khalil Benmouiza Co-supervisor University of Amar Telidji, Laghouat, Algeria (Bibliotheque centrale -Unversite de Laghouat, 2021)
In this thesis, diverse control methodologies are proposed for the control of the boost converter in order to improve the proton exchange membrane fuel cell (PEMFC) output power quality. The main aim is to keep the PEMFC power system operating at an adequate power point of the operating zone. This zone was created by the researchers at which up to more than 90% of the maximum generated power could be extracted, due to the non-linearity of the proton exchange membrane fuel cells (PEMFCs) and their affectation by the parameters such as cell temperature, the partial pressure of oxygen, the partial pressure of hydrogen and water content of the membrane. A non-linear controllers methodologies, have been proposed. First, the application of conventional linear controllers such as proportional (P), proportional-integral (PI) and proportional-integral-derivative (PID) did not succeed to drive the system to operate precisely in an adequate power point. Therefore, this thesis proposes a robust non-linear integral fast terminal sliding mode control (IFTSMC) aiming to improve the power quality generated by the PEMFC; besides, a digital filter is designed and implemented to smooth the signals from the chattering effect of the proposed controller. The stability proof of the IFTSMC is demonstrated via Lyapunov analysis. Comparative experimental results with the PI controller indicate that a reduction of 96% in the response time could be achieved using the suggested algorithm; where, up to more than 91% of the chattering phenomenon could be eliminated via the application of the digital filter. Second, a conventional first-order sliding mode control (SMC) is used. However, the chattering phenomenon, which is caused by the SMC leads to low control accuracy and heat loss in the energy circuits. In order to overcome these drawbacks, the quasi-continuous high-order sliding-mode controller (QC-HOSM) is proposed so as to improve power quality and the performance. The QC-HOSM controller stability is proven via the Lyapunov theory. In order to demonstrate the effectiveness of the proposed control scheme, exiii iv perimental results are compared with the conventional SMC. The obtained experimental results show that a chattering reduction of 84% is achieved using the QC-HOSM. The proposed controllers methodologies are designed for an experimental closed-loop system which consisted of a Heliocentric hy-Expert™ FC-50W, MicroLabBox DSPACE DS1202, DSPACE DS1104, step-up DC-DC power converter and programmable load . Third, a tuning and optimization technique has been proposed based on particle swarm optimization algorithm (PSO) in order to set the PID controller parameters in a good condition. Where, this latter is applied to a DC/DC boost converter in order to improve and optimize the PEMFC system power quality. Thus, due to its advantages compared with the conventional Ziegler-Nichols (ZN) tuning PID controller. The model and controllers have been implemented in MATLAB/SIMULINK environment. The proposed algorithm effectiveness has been studied successfully using a DC/DC stepup converter connected to a PEMFC. Study and comparison with the ZN are presented. The effectiveness of the proposed algorithm in transient, steady-state, dynamic responses, low overshoot and response time, especially against extremely load variation, have been demonstrated. Finally, a review of results shows that the suggested algorithm has significant advantages over conventional controllers. Keywords: proton exchange membrane, sliding mode control, integral fast terminal sliding mode control, digital filter, quasi-continuous high-order sliding-mode control, DC/DC step-up converter, particle swarm optimization algorithm, Ziegler-Nichols method.